The effectiveness of automated adjustment of inspired oxygen in preterm infants receiving respiratory support compared with manual: A systematic review and meta‐analysis - Yihan Zhang; Yuxuan Du; Yuan Shi (Pediatric Discovery)
Abstract Preterm infants may need supplemental oxygen due to immature lungs. Regardless of the type of oxygen therapy used, bedside clinicians frequently adjust the FiO2 level. Automatic oxygen management is progressively developing as a viable alternative to these corrections. The purpose of this study is to compare the efficacy and safety of automated versus manual oxygen control in preterm infants receiving respiratory support. All the studies were searched from PubMed, Web of Science, Cochrane Library, Embase, CNKI, Wan Fang, VIP, and CBM on 7 May 2022. PICOS criteria were as follows: (P) participants were preterm infants receiving respiratory support; (I) intervention was automatic oxygen control; (C) comparator mode was manual oxygen control; (O) the primary outcome was the percentage of time within the target pulse oxygen saturation range; (S) randomized clinical trials. Sixteen studies were included in this meta‐analysis. The results showed that automated oxygen control can increase the percentage of time spent within the target SpO2 range while reducing the percentage of time spent above the target SpO2 range, the percentage time of hypoxemia, and manual FiO2 adjustments/hour. No significant difference was observed in the percentage of time spent below the target SpO2 range, incidence of bradycardia, and the mean SpO2 or mean FiO2 level. Automatic oxygen control can improve preterm infants' oxygen saturation, reduce periods of hypoxemia and the percentage of time spent above the target SpO2 range, and ease the workload of medical staff without affecting the mean FiO2 and mean SpO2 levels.